PENYUSUNAN LAPORAN KEUANGAN BENGKEL LAS SETIAWAN TEKNIK BERBASIS SAK EMKM - B1033131022, Dewi Yuliansyah (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
Financial Accounting Standards Micro, Small, and Medium Entitties (SAK EMKM) is an accounting standard that arranged for fill necessary finance reporting of micro, small, and medium entities. This research was designed to produce a simple financial statements format based on SAK EMKM for MSMEs and know what factors  that be obstacle caused MSMEs not apply SAK EMKM. The object of this research is Setiawan Teknik Welding Workshop that located in Pontianak city that engage in welding trade.This research use descriptive qualitative approach and data collection technique that used is interview, documentation study, and literature study. From  result of research conducted, concluded that financial statements of Setiawan Teknik Welding Workshop are  still far from SAK EMKM because the financial entry only have the shape receipt note and  expend note in a simple. While factors that be obstacle so MSMEs not apply SAK EMKM are because not enough knowledge of accounting and existence of SAK EMKM and less control from government or related institute. Keywords : SAK EMKM, Financial Statements, MSMEs